2005
DOI: 10.1253/circj.69.439
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Postischemic Regional Left Ventricular Diastolic Wall Motion Abnormalities or Delayed Relaxation Following Coronary Vasospasm on Global Diastolic Function

Abstract: bnormalities of left ventricular (LV) filling and relaxation are sensitive early signs of myocardial ischemia in acute experiments involving animals and humans. [1][2][3][4] It is reasonable to assume that good quantitative analysis methods should detect differences between ischemic and non-ischemic myocardium very accurately. A number of non-invasive indexes of diastolic function have been proposed by the analysis of M-mode echocardiograms, Doppler LV filling velocity patterns, and radionuclide ventriculogram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
1

Year Published

2007
2007
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 34 publications
2
13
0
1
Order By: Relevance
“…[13][14][15] In the present study, the mean CK-DI value for six LV segments in the normal subjects (30 ± 18 years) was 70.6%. This result indicated that approximately 70% of the maximum LV expansion Comparison between septal and free wall CK-DI in the four study groups.…”
Section: Ck-diastolic Index (Ck-di)supporting
confidence: 46%
See 2 more Smart Citations
“…[13][14][15] In the present study, the mean CK-DI value for six LV segments in the normal subjects (30 ± 18 years) was 70.6%. This result indicated that approximately 70% of the maximum LV expansion Comparison between septal and free wall CK-DI in the four study groups.…”
Section: Ck-diastolic Index (Ck-di)supporting
confidence: 46%
“…16 The CK-diastolic index (CK-DI) was defi ned as the degree of LV segmental expansion during the fi rst 30% of diastole, expressed as a percentage. [13][14][15] The mean CK-DI, septal CK-DI, and free wall CK-DI were calculated from the average CK-DI of all segments, septal segments (asp, sp, inf), and free wall segments (ant, lat, pst), respectively. For each subject, data obtained from three diastolic CK images were averaged.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7][8][9][10] It is frequently observed in patients with CAD presenting with LV asynergy. [23][24][25] Earlier studies have demonstrated the presence of abnormal diastolic function in patients with CAD without evidence of systolic wall motion abnormalities by radionuclide angiography or digitized cineangiography.…”
Section: Discussionmentioning
confidence: 99%
“…Both clinical [3][4][5] and animal studies [6][7][8][9][10] have demonstrated that PSS is related to myocardial ischemia.…”
Section: Editorial P 37mentioning
confidence: 99%